Integration of Hr systems into the admission process in a tech recruitment company: a case study - Carvalho, Lais Amaral Cunha de; Damm, Djoille Denner; Andrade, Eron Passos (Brazilian Journal of Production Engineering, 2025)
The automation of the initial flow of information in the hiring process at a tech recruitment company represents a step forward in the optimization of workflows. The proposal aims to replace manual tasks with an automated system via webhooks, with the aim of reducing operational costs, eliminating errors, rework and waste of human capital, in addition to increasing data accuracy and integrity. Automation also contributes to reducing the execution of low-complexity tasks by operational personnel, reallocating labor to more strategic and value-adding activities. This study addressed the challenges of the manual process, such as filling errors and rework, which are reasons for delays in the onboarding of new employees. Automation seeks to mitigate these problems, aiming at a more fluid integration between systems and data consistency. Financial viability was evidenced by the projected cost savings, which allows for better allocation of resources and frees up the Human Resources team for more strategic activities. Aligned with the principles of Industry 4.0, automation integrates digital technologies to improve data quality and integrity and real-time analysis, promoting digital transformation and continuous innovation, which contributes to sustainable and efficient growth.
Keywords: Automation; Admission; Information System; Webhooks